Forestry villages in the Russian North - social capital and subsistence at the margins - Moran, Dominique (Belgeo, 2016)
This paper focuses on conditions in forestry villages in the northern rayony of Perm’ oblast’, in European Russia, which form part of the Russian "Near North". It describes the collapse of the local forestry economy after 1991, and against the backdrop of these economic conditions, the paper then discusses the survival strategies being employed by the inhabitants of the villages of these rayony, such as outmigration, household bifurcation, use of domestic and environmental resources, and the importance of social capital. The paper draws some conclusions about the interplay between rural depopulation, social capital, and marginalisation in villages in these northern rayony. Cet article analyse la situation de villages forestiers dans la région nord de l’oblast de Perm (Russie d’Europe), qui font partie du "Proche-Nord" russe. Il décrit l’effondrement de l’économie forestière locale après 1991 et examine les stratégies de survie mises en œuvre dans ce contexte économique par les habitants des villages de ces régions, telles que l’émigration, la bifurcation des ménages, l’utilisation des ressources domestiques et environnementales, ainsi que l’importance du capital social. Il se termine par quelques conclusions sur l’interaction entre dépopulation rurale, capital social et marginalisation dans les villages de ces régions septentrionales.